Analisis Loan To Deposit Ratio, Capital Adequacy Ratio dan Return On Assets PT. Bank Pembangunan Daerah Sumatera Barat - Jhon Fernos; Elva Dona (JURNAL PUNDI, 2018)
The purpose of this research is to investigate and analyze condition of Loan to Deposit Ratio (LDR), Capital Adequency Ratio (CAR) and Return On Assets (ROA) on PT. Bank Pembangunan Daerah Provinsi Sumatera Barat. Type of this research is descriptive quantitative research. Type of data in the research is primary and secondary data. The population that is used in this research is PT. Bank Pembangunan Daerah Sumatera Barat finance report begin 2016 until 2017. Analyze data technical is used of this research to calculate Loan to Deposit Ratio (LDR), Capital Adequency Ratio (CAR) and Return On Assets (ROA).Loan To Deposit Ratio (LDR) at PT. Bank Pembangunan Daerah Provinsi Sumatera Barat in 2016 and 2017 indicates that the level of liquidity of PT. Bank Pembangunan Daerah Provinsi Sumatera Barat is healthy because it is in the healthy category set by BI is LDR ≤ 94.75%. Capital Adequacy Ratio (CAR) Condition of PT. Bank Pembangunan Daerah Provinsi Sumatera Barat  in the period 2016-2017 is healthy because it is in the healthy category set by BI that is CAR ≥ 8%. Return On Assets (ROA) at PT. Pembangunan Daerah Provinsi Sumatera Barat in the period 2016 is healthy because it is in the healthy category set by the BI of ROA ≥ 1.215%. But in the year 2017 seen from the value of Return On Assets is quite healthy because it is in the category of healthy enough set by the BI of ROA <1.215%